2015
DOI: 10.1177/1090198115577378
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Reducing Sitting Time in Overweight and Obese Older Adults

Abstract: Background Overweight and obese older adults have high sedentary time. We tested the feasibility and preliminary effects of a sedentary time reduction intervention among adults over age 60 with a body mass index over 27 kg/m2 using a nonrandomized one arm design. Methods Participants (N = 25, Mean Age = 71.4, Mean BMI = 34) completed an 8-week theory-based intervention targeting reduced total sitting time and increased sit-to-stand transitions. An inclinometer (activPAL™) measured the primary outcomes, chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 40 publications
11
101
4
Order By: Relevance
“…Gardiner et al (26) This study also found that older persons commonly replace sedentary behavior with lightintensity physical activity. These results have been confirmed in other studies (27,28). Given that it is difficult that disabled older adults, who are usually very sedentary, replace sitting time with moderate or vigorous physical activity (24), most interventions should focus on increasing light-intensity physical activity, such as household chores, gardening, walking at slow pace, or even doing in a standing position some habitual sedentary activities (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…Gardiner et al (26) This study also found that older persons commonly replace sedentary behavior with lightintensity physical activity. These results have been confirmed in other studies (27,28). Given that it is difficult that disabled older adults, who are usually very sedentary, replace sitting time with moderate or vigorous physical activity (24), most interventions should focus on increasing light-intensity physical activity, such as household chores, gardening, walking at slow pace, or even doing in a standing position some habitual sedentary activities (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…In another study where older adults were specifically told to restrict TV time to 30 min/day, TV time decreased from 322 to 16 min/day 81. Finally, three studies reported an increase in the number of breaks in ST95 99 or sit to stand transitions 96. In most of the studies, the intervention also resulted in a significant increase in physical activity, particularly when assessed by self-report.…”
Section: Methodsmentioning
confidence: 99%
“…Interventions have been successful in reducing older adults' sedentary behavior (e.g., 9 to 76 min/day via self-reported behavior; 24 to 35 min/day via objectively measured behavior) [5][6][7][8][9]. These interventions typically require interventionists with specialized training, behavioral feedback from expensive activity monitors that are not commercially available, expensive individual behavior coaching, or extensive group counseling.…”
Section: Interventions To Reduce Older Adults' Sedentary Behaviormentioning
confidence: 99%